2011
DOI: 10.1021/cm201619y
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Zeolite Nanocrystal Seeds in the Synthesis of Mesoporous Catalysts with Zeolite Wall Structure

Abstract: Mesoporous titania-silica catalysts were prepared by hydrothermal conversion from synthesis solutions containing a zeolite structure directing agent (TPA+) and a porogen (CTA+). Syntheses were carried out with and without addition of zeolite seeds (i.e., TS-1 and Sil-1 nanocrystals). Catalysts prepared in the presence of zeolite nanocrystal seeds have greater proportions of tetrahedrally coordinated titanium, which correlate well with the detection of zeolite SBU fragments and ring-structure by TOF-SIMS and FT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 87 publications
4
32
0
Order By: Relevance
“…The permeability of the membranes was tested by a soap-film flow meter at room temperature. The benzene and styrene hydroxylation were carried out in a homemade reactor with details described elsewhere [8,44]. [45].…”
Section: Characterizationmentioning
confidence: 99%
See 4 more Smart Citations
“…The permeability of the membranes was tested by a soap-film flow meter at room temperature. The benzene and styrene hydroxylation were carried out in a homemade reactor with details described elsewhere [8,44]. [45].…”
Section: Characterizationmentioning
confidence: 99%
“…Pedernera et al [24] have reported that the inclusion of a zeolite precursor precursor during the mesoporous membrane synthesis led to partial zeolite incorporation into the porous structure. On the other hand, the Sil-1 particle seeds could promote the incorporation of zeolite secondary building unit fragments from the solution [44]. Therefore, the Sil-1 nanoparticles loaded on the support would be beneficial for embedding the zeolite units in the mesopore walls.…”
Section: Synthesis Of Ti-containing Mesoporous Membranementioning
confidence: 99%
See 3 more Smart Citations